The genome of Bacillus tequilensis EA-CB0015 sheds light into its epiphytic lifestyle and potential as a biocontrol agent - Cuellar-Gaviria, Tatiana Z.; García-Botero, Camilo; Ju, Kou-San; Villegas-Escobar, Valeska (Frontiers in Microbiology, 2023)
Different Bacillus species have successfully been used as biopesticides against a broad range of plant pathogens. Among these, Bacillus tequilensis EA-CB0015 has shown to efficiently control Black sigatoka disease in banana plants, presumably by mechanisms of adaptation that involve modifying the phyllosphere environment. Here, we report the complete genome of strain EA-CB0015, its precise taxonomic identity, and determined key genetic features that may contribute to its effective biocontrol of plant pathogens. We found that B. tequilensis EA-CB0015 harbors a singular 4 Mb circular chromosome, with 3,951 protein-coding sequences. Multi-locus sequence analysis (MLSA) and average nucleotide identity (ANI) analysis classified strain EA-CB0015 as B. tequilensis. Encoded within its genome are biosynthetic gene clusters (BGCs) for surfactin, iturin, plipastatin, bacillibactin, bacilysin, subtilosin A, sporulation killing factor, and other natural products that may facilitate inter-microbial warfare. Genes for indole-acetic acid (IAA) synthesis, the use of diverse carbon sources, and a multicellular lifestyle involving motility, biofilm formation, quorum sensing, competence, and sporulation suggest EA-CB0015 is adept at colonizing plant surfaces. Defensive mechanisms to survive invading viral infections and preserve genome integrity include putative type I and type II restriction modification (RM) and toxin/antitoxin (TA) systems. The presence of bacteriophage sequences, genomic islands, transposable elements, virulence factors, and antibiotic resistance genes indicate prior occurrences of genetic exchange. Altogether, the genome of EA-CB0015 supports its function as a biocontrol agent against phytopathogens and suggest it has adapted to thrive within phyllosphere environments.